2014
DOI: 10.1063/1.4902111
|View full text |Cite
|
Sign up to set email alerts
|

Collective flow dynamics across a bacterial carpet: Understanding the forces generated

Abstract: Bacterial carpets consist of randomly anchored uni-polar-flagellated sodium-motive bacterial matrix are prepared by flow deposition. Collective flow dynamics across the bacterial carpets are probed with optical tweezers-microsphere assay. Around the center of a uniform bacterial cluster, collective forces that pull microsphere towards carpet surface are detected at a distance of 10 μm away from carpets. At sodium-motive driving over a critical value, the force magnitudes increase abruptly, suggesting a thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…These previous studies have clearly demonstrated the possibility of using immobilized bacteria to drive fluid flow 14,24,25,27,28 . In order to engineer the generated flow, one has to precisely control the position and orientation of immobilized bacteria.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…These previous studies have clearly demonstrated the possibility of using immobilized bacteria to drive fluid flow 14,24,25,27,28 . In order to engineer the generated flow, one has to precisely control the position and orientation of immobilized bacteria.…”
Section: Introductionmentioning
confidence: 91%
“…In a pioneering experiment, Darnton et al immobilized motile bacteria on an open surface to form a densely packed monolayer, called a bacterial carpet; rotating flagella of the tethered bacteria generate strong flow near the activated surface 14 . In the following studies, bacterial carpets have been used to pump fluid through a micro-channel 24 , to enhance mixing in micro-fluidic devices 25 , and to investigate collective dynamics of hydrodynamically coupled cells [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…We studied the emergence of large-scale recirculation by a carpet of force-free actuators. Surprisingly, finite clusters of randomly oriented bacteria drive non-diffusive currents, in contracts with ciliary arrays [73][74][75][76] and grafted cells [77][78][79][80] where alignment is essential for microbiological transport [SI §2C]. Moreover, in the context of diversity in carpet architecture, it might be beneficial for an individual organism not to generate a flow to maximise the collective flux.…”
Section: Discussionmentioning
confidence: 99%
“…Above we found that a carpet of randomly oriented dipoles does generate a net drift, for any finite carpet size. However, in ciliary arrays [73][74][75][76] and grafted cells [77][78][79][80] the force alignment is essential for microbiological transport. To highlight this, note that a carpet of Stokeslets (S3), u S (p s ) = B(r, r s ) · p s , oriented randomly in the x-y directions, p s = cos φ sx + sin φ sŷ , does not generate a net drift, for any carpet size;…”
Section: Carpet Of Stokesletsmentioning
confidence: 99%
“…Since the pioneering work by Kim and Breuer on self-organizing bacteria carpets leading to microfluidic pumping [1][2][3][4][5], the phenomena of bacterial self-organization resulting in spontaneous fluid flow are meanwhile readily reproduced and are already exploited on a level approaching applications [6][7][8][9][10][11][12]. In a qualitative picture, the mechanism responsible for all these spontaneously driven flows is considered to be collective coordination between individual bacteria caused by fluid flow that is generated by their flagella.…”
Section: Introductionmentioning
confidence: 99%